Stratification of clear cell renal cell carcinoma by signaling pathway analysis. (April 2014) - Cremona, Mattia; Espina, Virginia; Caccia, Dario; Veneroni, Silvia; Colecchia, Maurizio; Pierobon, Mariaelena; Deng, Jianghong; Mueller, Claudius; Procopio, Giuseppe; Lanzi, Cinzia; Daidone, Maria Grazia; Cho, William CS; et al.
Abstract : Investigation of cell signaling pathways in 16 clear cell renal cell carcinomas to identify groups based on commonly shared phosphorylation-driven signaling networks. Using laser capture microdissection and reverse-phase protein arrays, we profiled 75 key nodes spanning signaling pathways important in tumorigenesis. Analysis revealed significantly different (P < 0.05) signaling levels for 27 nodes between two groups of samples, designated A (4 samples; high EGFR, RET, and RASGFR1 levels, converging to activate AKT/mTOR) and B (12 samples; high ERK1/2 and STAT phosphorylation). Group B was further partitioned into groups C (7 samples; elevated expression of LC3B) and D (5 samples; activation of Src and STAT). Network analysis indicated that group A was characterized by signaling pathways related to cell cycle and proliferation, and group B by pathways related to cell death and survival. Homogeneous clear cell renal cell carcinomas could be stratified into at least two major functional groups.